Multi‐shelled Hollow Nanospheres of SnO2/Sn@TiO2@C Composite as High‐performance Anode for Lithium‐Ion Batteries. Issue 17 (6th July 2021) - Zhao, Wencai; Yuan, Yongfeng; Du, Pingfan; Zhu, Min; Yin, Simin; Guo, Shaoyi
Abstract: To overcome two main drawbacks of SnO2 as anode material in lithium‐ion batteries, low conductivity and poor cycling stability, SnO2 /Sn@TiO2 @C composite is prepared via one‐pot hydrothermal reaction to synthesize SnO2 /C precursor‐assembled hollow nanospheres and then coated with TiO2 and resorcinol‐formaldehyde resin. After calcination, multi‐shelled hollow nanospheres of SnO2 /Sn@TiO2 @C are formed. When used as anode material in lithium‐ion batteries, the as‐prepared composite exhibits high discharge capacity of 1565 mAh g −1 at 0.5 A g −1 . After 300 cycles at 1 A g −1, the discharge capacity still reaches 961 mAh g −1 with capacity fading rate of just 0.11 % per cycle. The average discharge capacity reaches 395 mAh g −1 even at 5 A g −1 . The superior lithium storage performance mainly benefits from the unique multi‐shelled hollow nanosphere structure. The coating TiO2 and amorphous carbon increase structural and cycling stabilities of SnO2 /Sn hollow nanospheres. The outermost carbon shell further enhances electronic conductivity of the composite. The hollow nanosphere structure also endows SnO2 /Sn nanoparticles with high electrochemical activity. This work proposes a feasible synthesis and structure design strategy for the development of advanced SnO2 ‐based composite materials. Abstract : SnO2 based advanced composite material : Hollow mesoporous assembly of SnO2 nanomaterial and carbon is efficiently synthesized by a one‐pot process. Further coating the hollow assembly with TiO2 and carbon, improves the lithium storage performance of the composites remarkably, including reversible capacity and cycling performance. Effects of the TiO2 and carbon coating are studied in detail, and the related electrochemical mechanism of the composite is demonstrated.